Formulary management challenges and opportunities: 2020 and beyond ‐ an opinion paper of the drug information practice and research network of the American College of Clinical Pharmacy. Issue 1 (4th October 2020) - Johnson, Steven T.; Gosser, Rena A.; Kier, Karen L.; Anderson, Keri C.; Douglas, Janine S.; Heindel, Gregory A.; Majerczyk, Daniel; Manian, Radha; Thornby, Krisy‐Ann
Abstract: Formulary management systems in hospitals and health‐systems serve to ensure that medications are rigorously evaluated for efficacy, safety, and value. The increased complexity of these systems, along with the broadening of items for formulary inclusion, poses unique challenges and opportunities for the development of innovative formulary management processes. Pharmacists are challenged to evaluate different types of medications that are not all small molecule entities as well as deal with medication shortages that can impact patient care. The authors review unique formulary aspects of biosimilars, gene therapy, rare disease treatments, outpatient therapies, and formulary‐related challenges/opportunities with drug shortages. Core strategies for formulary management and drug shortage mitigation techniques in closed formulary settings are discussed. This information is intended to guide formulary decision‐makers and other clinicians to effectively manage health‐system formularies in 2020 and beyond.